Constitutive models for numerical analysis of the short- and long-term behavior of geosynthetics and mechanical damage - Lombardi, G. (2022)
Analyse the tensile response of different geosynthetics; Apply constitutive models to describe the nonlinear tensile behaviour of these materials in the short- and the long-term, before and after damage; Propose model parameters for intact and damaged specimens.